An investigation of vtx2 bacteriophage transduction to different Escherichia coli patho-groups in food matrices and nutrient broth. (December 2017) - Nyambe, Sepo; Burgess, Catherine; Whyte, Paul; Bolton, Declan
Abstract: This study investigated bacteriophage (phage) mediated transfer of the vtx 2 gene from a donor Escherichia coli (C600φ3538(Δvtx2 ::cat)) to enteropathogenic (EPEC), enterotoxigenic (ETEC), enteroaggregative (EAEC), enteroinvasive (EIEC) and diffusely adherent (DAEC) E. coli strains in LB broth, milk, ground beef and lettuce. Two bacterial concentrations for both the E. coli donor and recipient strains, 3 and 5 log10  CFU/ml (LB broth and milk)/g (beef) or/cm 2 (lettuce), were used. When transductants were obtained, the location of insertion of the phage (insertion sites wrbA, yehA, sbcB, yecE and/or Z2577) in the E. coli chromosome was investigated by PCR. The vtx 2 gene was readily transferred to EAEC O104:H4 (E99518) in all matrices and inserted into the chromosome at the sbcB locus. At higher cell concentrations, transductants were also obtained with ETEC E4683, ETEC E8057 (insertion site unknown) and DAEC O75:H- E66438 (insertion site unknown) in LB broth and milk. It was concluded that the vtx 2 gene may be transferred by bacteriophage to different E. coli pathotypes in laboratory and food matrices, resulting in the spread of the vtx 2 gene and the emergence of novel foodborne pathogens. Highlights: The vtx 2 gene was readily transferred in all matrices. The phage integrated into the EAEC O104:H4 (E99518) chromosome at the sbcB locus. Transductants were also obtained with ETEC E4683, ETEC E8057 and DAEC O75:H- E66438 in LB broth and milk.